Efektivitas Media Sosial dalam Mempromosikan Pendidikan Tinggi Berbasis Vokasional Kepada Calon Mahasiswa - Septiana, Vita; Murtiningsih, Bertha Sri Eko; Astagini, Nuria (Jurnal Pustaka Komunikasi, 2025)
Social media is currently used as a promotional tool for various services, including higher education. One of the higher education institutions utilizing social media is the Indonesian Television Academy (ATVI). This study aims to measure the effectiveness of using social media in promoting ATVI to prospective students. The study employed a quantitative method by conducting a survey involving 131 prospective students as respondents who participated by filling out questionnaires. The data were analyzed using SPSS software to produce descriptive statistics, regression analysis, and ANOVA to understand the relationship between social media effectiveness and ATVI promotion. The results show that social media has proven to be effective in promoting ATVI to prospective students. Instagram emerged as the most effective platform, with advertisement scores achieving a mean value of 3.43. Other social media platforms, such as TikTok, YouTube, and Facebook, received mean scores below Instagram. Additionally, prospective students expressed interest in studying at ATVI after viewing the institution's Instagram account. The findings indicate a positive and significant relationship between social media effectiveness and ATVI promotion. Social media platforms play an important role in shaping the perceptions and decisions of prospective students, making them a strategic tool for effectively promoting ATVI to potential students.